(untitled) (Advances in Systems Science and Applications, 2022)
The HTA progress requires analyses of existing and forthcoming needs as well as the development of tools meeting these needs. The proposed research presents hierarchical scheme for HTA development created based on Environmental Scanning and Analytic Hierarchy Process (AHP). The scheme presents the overall prognosis of HTA development indicating the key blocks of needs and relevant tools. Each of these tools are considered to be exclusively important for HTA development. Local registries are considered to be the priority for further HTA improving meeting more needs and providing less risks comparing to other tools.